Evaluation of Spirulina Platensis Extract Effect on the Expression Level of Apoptosis-Related Gene (Drp1) and Regulation Programmed Cell Death in Human Gastric Adenocarcinoma Cell Line (AGS) - Farkhondeh Mohammadi; Leila Rouhi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Gastric adenocarcinoma ranks among the most prevalent cancers globally. This aggressive malignancy often leads to poor treatment outcomes for the patients. This study investigated the effect of  Spirulina platensis extract on the expression level of apoptosis-related gene Drp1 and its role in regulating programmed cell death in the human gastric adenocarcinoma cell line AGS Methods: AGS gastric adenocarcinoma cells were cultured in DMEM-F12 medium supplemented with 10% bovine serum. The cells were treated in 40 µg/mL of Spirulina extract and incubated for 48 hours. Apoptosis was analyzed using flow- cytometry with an Annexin V-FITC/PI kit, following the manufacturer's protocol. Moreover, AGS cells were incubated with the same concentrations of Spirulina extract for 48 hours to evaluate Drp1 gene expression, which was analyzed using Real Time PCR. Results: The Annexin V test results showed that treatment with 40 µg/mL of Spirulina extract induced apoptosis in AGS cells. Furthermore, this treatment significantly increased the expression of Drp1 gene in the experimental group compared to the control group. Conclusion: The results indicate that Spirulina extract can enhance the bioavailability of gastric adenocarcinoma cells by inducing apoptosis pathway. Consequently, Spirulina extract seems to be used as an anticancer agent for treating gastric adenocarcinoma.